2012
DOI: 10.1002/jso.21935
|View full text |Cite
|
Sign up to set email alerts
|

The quest for diagnostic molecular markers for thyroid nodules with indeterminate or suspicious cytology

Abstract: Thyroid nodules are very common and fine needle aspiration (FNA) is a very sensitive means of diagnosis. However, its limitations include the fact that the cytology reports are often indeterminate or suspicious only. The quest for adjunctive measures to improve its specificity has been ongoing for decades, but significant results have remained elusive. The potential use of diagnostic molecular markers appears to be the most promising area of research at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 85 publications
0
23
0
Order By: Relevance
“…Although different opinions exist, ICC is considered by some scholars as a molecular test that detects cellular changes at molecular levels [7][8][9] and is included in this review for completeness. Immunocytochemistry is available in most pathology laboratories, is less time consuming, is less expensive, and practicing pathologists are confident in interpreting its results.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Although different opinions exist, ICC is considered by some scholars as a molecular test that detects cellular changes at molecular levels [7][8][9] and is included in this review for completeness. Immunocytochemistry is available in most pathology laboratories, is less time consuming, is less expensive, and practicing pathologists are confident in interpreting its results.…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Despite a low sensitivity, BRAF mutation specificity is quite high with a false positive rate of only 0.2%. 54,55) A more recent meta-analysis, summarizing the results of 6 studies and including 2800 malignant and benign lesions, reported a BRAF mutation specificity of 97.9% and a positive predictive value of 99.9%. Only seven false positive results were identified in three different studies.…”
Section: Braf Mutationmentioning
confidence: 99%
“…For thyroid cancer, BRAF and RAS mutations and RET/ PTC and PAX8/PPARc rearrangements, associated with the abnormal regulation of miRNAs, constitute the most implicated molecular alterations identified in PTC [19][20][21][22][23]. BRAF is the most common mutation detected in PTC with a frequency of 45 % [24 • ] and is rare in follicular adenoma and carcinoma [16].…”
Section: Molecular Markersmentioning
confidence: 99%
“…The RAS oncogene (HRAS, KRAS and NRAS) encodes small GTP-ase proteins involved in signal transduction [21] and has predominance in follicular neoplasms, including follicular adenoma, follicular carcinoma and the follicular variant of PTC [22,26].…”
Section: Molecular Markersmentioning
confidence: 99%
See 1 more Smart Citation